2007
DOI: 10.1183/09031936.00002607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the role of mycobacteria in sarcoidosis: a meta-analysis

Abstract: The aetiology of sarcoidosis is currently unknown. Due to the clinical and histological similarities between sarcoidosis and tuberculosis, the role of mycobacteria has been repeatedly investigated as an aetiological agent for sarcoidosis. The current meta-analysis aimed to evaluate the available molecular evidence on the possible role of mycobacteria in the development of sarcoidosis.The MEDLINE, EMBASE, CINAHL, DARE and CENTRAL databases were searched for relevant studies published from 1980 to 2006, and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 68 publications
4
120
0
2
Order By: Relevance
“…This is supported by the fact that the mycobacterial cell wall agent tuberculostearic acid has been isolated in sarcoid granulomas [14]. Other agents like Propionibacterium acnes and several viruses have been implicated as well.…”
Section: Discussionmentioning
confidence: 50%
“…This is supported by the fact that the mycobacterial cell wall agent tuberculostearic acid has been isolated in sarcoid granulomas [14]. Other agents like Propionibacterium acnes and several viruses have been implicated as well.…”
Section: Discussionmentioning
confidence: 50%
“…In a pooled analysis, 231 out of 874 patients with sarcoidosis were positive for mycobacterial (MTB or non-MTB) nucleic acid (83). The authors concluded that, despite evidence of a reporting bias, the odds ratio in their analysis suggested an association between mycobacteria and sarcoidosis (83).…”
Section: Nucleic Acid Identificationmentioning
confidence: 98%
“…Moreover, monoclonal antibodies to gram-negative bacteria can cross-react with HLA-B27 in SpA [6] while mycobacterial infection could possibly be related to sarcoidosis. [7] Although various viral and bacterial agents have been reported, some agents, for example propriobacterium acnes, have been isolated from tissues in both diseases. [5] Acute anterior uveitis is the most frequent extraarticular manifestation in patients with AS, [8] and this can be the initial symptom of SpA, especially if the patients have been diagnosed with uSpA.…”
Section: Discussionmentioning
confidence: 99%